Monetary and Fiscal Policy Interaction in the Euro Area with different assumptions on the Phillips curve - Peter Bofinger; Eric Mayer (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2004)
In this paper we carry over a static version of a New Keynesian Macro Model to a monetary union. For a similar approach see Uhlig (2002). We will show in particular that a harmonious functioning of a monetary union critically depends on the correlation structure of shocks that hit the currency area. Additionally a high degree of integration in product markets is advantageous for the ECB as it prevents that national real interest rates can drive a wedge between macroeconomic outcomes across member states. In particular small countries are in a vulnerable and therefore in need for fiscal policy as an independent stabilization agent with room to breath.
Keywords: E50; H70; E60; 330; Monetary policy; inflation targeting; fiscal policy; policy coordination; freeriding; Geldpolitik; Finanzpolitik; Internationale wirtschaftspolitische Koordination; Ungleichgewichtstheorie; Phillips-Kurve; Europäische Wirtschafts- und Währungsunion; Theorie